Identifikasi Zat Klorin pada DEDORAN bermerek yang Diperjualbelikan Di Mall Wisata Uit Makassar - Suharsih Thahir (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2017)
Chlorine is the result of human engineering that provides many benefits both good and bad life. The use of chlorine in the deodorant causes irritation to the skin and causes burns and piercing sensations, inflammation and vesicle formation. The purpose of this study was to identify chlorine substances in branded deodorants traded in Mall Wisata UIT Makassar. The samples of deodorant studied were 5 samples. Based on the results of the research, there were positive results containing chlorine from 5 samples studied, because the sample solution color change after added reagent solution Cl2-14 drops and Cl2-2 2 drops. It is suggested to the public to be more careful in choosing deodorant and for the next researcher to examine the level of branded deodorant.